Graphene Synthesis from Empty Palm Oil Bunch for Modifying Screen Printed-Carbon Electrode Glucose-Biosensor - Khofiyya, Nida An; Al Khoiriah, Nidzomah Dina; Nadifah, Umi; Afryansyah, Afryansyah (Proceeding International Conference on Religion, Science and Education, 2025)
Glucose is a monosaccharide that is the energy source and controls vital activities in the body. Therefore, continuous glucose level monitoring is needed to know the representation of the body’s condition. A commonly used method for monitoring is the SPCE biosensor for practical and economical reasons. The effectiveness of SPCE biosensor performance is determined by its constituent materials, so this research was conducted to determine how the graphene synthesis process from empty oil palm bunches (EOPB) and its application to SPCE can affect the performance of glucose biosensors. Graphene was chosen based on its superior characteristics, while EOPB was used as raw material because of its content such as lignin and cellulose, and its abundant availability. This research is quantitative-experimental with the object, EOPB. Graphene synthesis was carried out using the liquid phase exfoliation (LPE) method while electrode printing on the biosensor using the drop-casting method. The results of the characterization of graphene synthesis with SEM-EDS show a layer of graphene sheets with a single-layer hexagonal planar structure with an average distribution size of small particles, 0.023 ± 0.019 µm. The distribution of elements in graphene synthesis is dominated by carbon, which is 52.1%, indicating the existence of carbon allotrope, namely graphene. The performance of the SPCE biosensor was tested using amperemetry technique with three variations of graphene concentration (P1, P2, and P3) and two variations of glucose solution concentration (L1 and L2). The test results showed a positive relationship between increasing the concentration of graphene and glucose solution with the strong electric current produced, indicating that the SPCE biosensor is stable and good at reading electric current.